Technological and geographical patterns in the choice of cooperation partner - Andreas Meder (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
A key issue of dfferent streams of economic literature is to determine the impact of certain dimensions of proximity on the cooperative behavior of actors and, thus, on interactive learning processes. This paper is a quantitative study on the impact of technological and geographical proximity on the choice of the cooperation partner. Patents that were filed for Germany in the years 1998 to 2003 are used to identify the impact of both dimensions of proximity as well as their interplay. It can be shown that an increasing proximity in either of these dimensions has an independent positive impact on the cooperation probability.
Keywords: C30; L14; O32; 330; Cooperation; cognitive proximity; geographical proximity; Unternehmenskooperation; Forschungskooperation; Entfernung; Technologiewahl; Patent; Deutschland